Methods of printing heterostructured materials by combinatorial slip surface printing, heterostructured materials, and heat sensing and harvesting devices

CN118789956BActive Publication Date: 2026-10-27QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410803293.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2026-10-27
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

尽管一些研究已经将纸张推广为电子设备的柔性基板,但组装为热电器件需要通过剪裁与粘贴进行组装的方法,目前已得到广泛应用的热电材料如金属碲、金属碲化物和硒化物等,通常价格昂贵,在后期剪裁与连接过程中难以避免材料的浪费,制备工艺复杂,成本较高,并且难以实现批量化生产,亟需研究新的制备工艺

Benefits of technology

[0021]1、本发明通过组合式滑移表面印刷异质结构材料的方法,通过真空抽滤的方式将两种异质结构材料进行组装,制备工艺简便,生产成本较低,能够满足大规模批量生产的要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118789956B_ABST
    Figure CN118789956B_ABST
Patent Text Reader

Abstract

The application provides a method for printing a heterostructure material through a combined sliding surface, a heterostructure material and a heat sensing and collecting device, and relates to the field of heterostructure material preparation; wherein the heterostructure material is prepared through a method combining a movable sliding surface and a fixed sliding surface in a vacuum filtration mode, and specifically comprises the following steps: S1, preparing a polydimethylsiloxane prepolymer ink; S2, preparing a fixed sliding surface; S3, preparing a movable sliding surface; S4, first thermoelectric material controllable patterning assembly; and S5, second thermoelectric material controllable patterning assembly and formation of a heterostructure material. Through the method for printing a heterostructure material through a combined sliding surface, two kinds of heterostructure materials are assembled through a vacuum filtration mode, the preparation process is simple, the production cost is relatively low, and the requirements of large-scale batch production can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heterostructure material preparation, and particularly to a method for printing heterostructure materials by combined sliding surfaces, the heterostructure materials, and a heat sensing and collection device. Background Technology

[0002] Slip surfaces are material surfaces with special functions and have been widely used in anti-icing, anti-fouling, and microfluidic transport. Current methods for preparing slip surfaces are limited to etching and surface grafting, which are typically costly, require complex operations, and involve processing the entire surface, preventing patterned applications. This invention uses polydimethylsiloxane (PDMS) as the ink for preparing slip surfaces and employs direct-write printing to prepare slip surfaces on polytetrafluoroethylene (PTFE) microporous membranes. By controlling printing parameters and curing conditions, the influence of wetting ridges on the flexible surface is reduced, resulting in slip surfaces with excellent slip properties. Strong acid corrosion and high-temperature experiments demonstrate the stability and reusability of the slip surfaces prepared by this method. The successful preparation of direct-write printed slip surfaces provides a low-cost, highly flexible new method for patterned slip surfaces and offers a reliable reference for assembling patterned nanomaterials.

[0003] Thermoelectric generators can generate electricity under temperature gradients, a pollution-free method that can produce useful power from waste heat or solar radiation, showing broad application prospects. Typically, thermoelectric materials need to be mixed with polymers or organic compounds to obtain flexible and independent thermoelectric devices. Although some research has promoted paper as a flexible substrate for electronic devices, assembling it into thermoelectric devices requires a cutting and gluing method. Currently widely used thermoelectric materials, such as metal telluride, metal telluride, and selenide, are usually expensive, and material waste is unavoidable during the later cutting and joining processes. The manufacturing process is complex, costly, and difficult to achieve mass production, necessitating the research of new manufacturing processes. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention provides a method for printing heterogeneous structural materials using a combined sliding surface. This method involves using a movable sliding surface for direct writing printing, which is then adhered to a fixed sliding surface for direct writing printing. By adjusting the position covered by the movable sliding surface, a heterogeneous structure of two different materials can be deposited within a confined space on a single surface.

[0005] In a first aspect, the present invention provides a method for printing heterogeneous structural materials using a combination of movable and fixed sliding surfaces, wherein the heterogeneous structural materials are prepared by vacuum filtration using a combination of movable and fixed sliding surfaces, specifically including the following steps:

[0006] S1. Preparation of polydimethylsiloxane prepolymer ink: Weigh polydimethylsiloxane prepolymer and curing agent according to the set ratio, stir at room temperature for 10-20 minutes, put into a vacuum drying oven, and then vacuum store for a set time to obtain polydimethylsiloxane prepolymer ink.

[0007] S2. Preparation of a fixed sliding surface: Treat the polytetrafluoroethylene microporous filter membrane with 50-100W O2 plasma for 5-10 minutes. Fix the treated polytetrafluoroethylene microporous filter membrane on a direct writing printing stage as a printing substrate. Inject the polydimethylsiloxane prepolymer ink into the ink container. Print according to the preset printing steps under a printing pressure of 0-50psi. Place the printed product in a constant temperature heating stage and heat until the polydimethylsiloxane prepolymer ink is cured to obtain a fixed sliding surface.

[0008] S3. Preparation of a movable sliding surface: The polyester film and trimethoxyfluorosilane liquid are placed in a vacuum drying dish for pretreatment. The pretreated polyester film is printed and placed on a heating table and heated until the polydimethylsiloxane prepolymer ink is cured. The movable sliding surface is then separated from the polyester film to obtain the movable sliding surface.

[0009] S4. Controllable patterned assembly of the first thermoelectric material: According to the patterning requirements, the movable sliding surface prepared in step S3 is attached to the fixed sliding surface prepared in step S2 and fixed on the funnel. After being fully wetted, the first dispersion solution is poured into the funnel and vacuum filtered to complete the controllable patterned assembly of the first thermoelectric material and obtain a combined sliding surface with the first thermoelectric material.

[0010] S5. The second thermoelectric material is controllably patterned and assembled to form a heterogeneous structure material: The movable sliding surface prepared in step S3 is moved to the area partially covered by the first thermoelectric material on the combined sliding surface with the first thermoelectric material prepared in step S4 and fixed on the funnel. After being fully wetted, the second dispersion solution is poured into the funnel for vacuum filtration. The second thermoelectric material is controllably patterned and assembled to form a heterogeneous structure material.

[0011] Preferably, the first set ratio is a weight ratio of 10:1, and the first set time is 30±5 min.

[0012] Preferably, in step S1, the polydimethylsiloxane prepolymer and the curing agent undergo a crosslinking reaction after being mixed, and the pressure of the vacuum drying oven is 0.5-1 MPa.

[0013] Preferably, in step S2, the pore size of the polytetrafluoroethylene microporous filter membrane is adjusted according to the size of the dispersed phase particles in the first dispersion solution and the second dispersion solution, the needle diameter used in the printing process is selected according to the resolution requirements of the printed pattern, and the funnel is a sand core funnel.

[0014] Preferably, in step S2, the heating temperature of the heating table is 85-90℃, the drying temperature of the drying oven is 85-90℃, and the drying time is 12-13h.

[0015] Preferably, in step S2, the size of the polyester film sheet is 6×6cm. 2 The pretreatment involves evacuating the vacuum drying dish to a vacuum state, placing it in a drying oven at 90±5℃ for 10-12 hours, and then ultrasonically cleaning it in a container filled with ethanol for 5-10 minutes.

[0016] Preferably, the first dispersion solution and the second dispersion solution are matrix solutions of heterogeneous structural materials, and the first dispersion solution and the second dispersion solution are deionized water, ethanol or methane.

[0017] A second aspect of the present invention provides a heterostructure material, which is prepared by a method of combined sliding surface printing of heterostructure materials.

[0018] A third aspect of the present invention provides a heat sensing and collection device comprising the aforementioned heterostructure material, wherein the heat sensing and collection device comprises the aforementioned heterostructure material, and the heat sensing and collection device is a PN alternating thermoelectric generator and a thermal sensor.

[0019] Preferably, the PN alternating thermoelectric generator is prepared by using an N-type selenium-doped bismuth telluride dispersion as the first dispersion solution and a P-type antimony telluride dispersion as the second dispersion solution when preparing the heterostructure material.

[0020] Compared with the prior art, the present invention has the following advantages:

[0021] 1. This invention uses a combined sliding surface printing method to assemble two heterogeneous structural materials by vacuum filtration. The preparation process is simple, the production cost is low, and it can meet the requirements of large-scale mass production.

[0022] 2. The present invention uses a method of printing heterogeneous structural materials on a combined sliding surface. By using a movable sliding surface printed by direct writing and a fixed sliding surface to cooperate with each other, a heterogeneous structure with two materials uniformly distributed is formed within a surface confinement. Moreover, the heterogeneous structural materials prepared by this method have good uniformity.

[0023] 3. The heat sensing and collection device prepared by the method of combined sliding surface printing heterogeneous structural materials in this invention has excellent durability and stability. The resistance change of the heat sensing and collection device under 6000 bending cycles with a displacement of 15mm is less than 0.2.

[0024] 4. The heat sensing and collection device prepared by the method of combined sliding surface printing heterogeneous structure materials in this invention has high sensitivity and a wide temperature response range. It can be applied to the preparation of thermal sensors or thermoelectric generators. Through actual application testing, the heat sensing and collection device, as a thermal sensor, responds to finger touch with a response time of 0.452s and a recovery time of 0.421s. The heat sensing and collection device can respond to human body temperature and hot water temperature, with a wide temperature response range.

[0025] 5. The heat sensing and collection device prepared by the present invention through the method of combined sliding surface printing of heterogeneous structural materials is assembled into a thermoelectric generator, which can generate open-circuit voltage under the action of temperature difference between hot and cold ends. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the overall process of the present invention;

[0027] Figure 2 This is a schematic diagram of the specific method flow of the present invention;

[0028] Figure 3 This is a schematic diagram of the thermodynamic mechanism of the PN heterostructure material of the present invention;

[0029] Figure 4 The graph shows the relationship between the crosslinking time and minimum printing pressure of polydimethylsiloxane prepolymer ink obtained by printing with printing needles of diameters of 100μm, 150μm and 300μm using the method of printing heterogeneous structural materials on combined sliding surfaces according to the present invention.

[0030] Figures 5a-5b These are infrared spectra of the polydimethylsiloxane prepolymer ink used in the method of printing heterogeneous materials on a combined sliding surface in this invention, at different curing times; wherein, Figure 5a This is the infrared spectrum at the start of curing. Figure 5b Infrared spectrum of a product cured for more than 10 minutes;

[0031] Figures 6a-6d This refers to the morphology of sliding surfaces with different degrees of curing and the instant deionized water droplets falling, used in the method of printing heterogeneous structural materials on combined sliding surfaces in this invention; wherein... Figure 6a A diagram showing the morphology of deionized water droplets falling onto an uncured, slipping surface. Figure 6b Morphological diagram of a droplet falling onto a sliding surface cured at 85°C for 1 minute. Figure 6c Morphological diagram of the slip surface cured at 85℃ for 2 min. Figure 6d Morphological diagram of a droplet falling onto a sliding surface cured at 85°C for 10 minutes.

[0032] Figures 7a-7d The diagram shows the contact angle morphology of deionized water droplets on sliding surfaces with different degrees of curing after a certain period of time; among them, Figure 7a This is a diagram showing the contact angle between an uncured sliding surface and a deionized water droplet after a certain period of time. Figure 7b and Figure 7c The images show the contact angles of the sliding surface after curing for a certain time and the contact angles of the surface after deionized water droplets have been dropped for a certain time. Figure 7d A diagram showing the contact angle between a fully cured sliding surface and a deionized water droplet after a certain period of time.

[0033] Figures 8a-8c These are scanning electron microscope (SEM) images of the sliding surface and the sample during the application of the method for printing heterogeneous structural materials using a combined sliding surface, as described in this invention; wherein, Figure 8a A fixed sliding template; Figure 8b It is a P-type structural unit; Figure 8c It is a PN-type structural unit; Figures 8d-8f Optical microscope images of the interface between polydimethylsiloxane prepolymer ink and N-type and P-type units, respectively.

[0034] Figures 9a-9e The scanning electron microscope (SEM) image and X-ray diffraction (EDS) image of the N-unit of the heat sensing and collection device in the application of the method of combined sliding surface printing heterogeneous structure materials of the present invention are shown below. Figure 9a A SEM image of N units; Figure 9b This is the element mapping diagram of Bi in unit N; Figure 9c Figure d shows the elemental mapping of Te in the N-cell; Figure e shows the elemental mapping of Se in the N-cell; Figure e shows the EDS spectrum of the N-cell.

[0035] Figures 10a-10d The scanning electron microscope (SEM) image and X-ray diffraction (EDS) image of the P-unit of the heat sensing and collection device in the application of the method of combined sliding surface printing heterogeneous structure materials of the present invention are shown below. Figure 10a SEM image of P cell; Figure 10b This is an element mapping diagram of Bi in unit P; Figure 10c Figure d shows the elemental mapping of Te in the P unit; Figure d is the EDS spectrum of the P unit.

[0036] Figures 11a-11d This invention relates to the application of a method for printing heterogeneous structural materials on a combined sliding surface, specifically for testing the bending performance of a heat sensing and collection device.

[0037] Figures 12a-12d This invention relates to the application of a heat sensing and collection device for thermoelectric performance testing of a heat sensing and collection device using a combined sliding surface printing method for heterogeneous structural materials.

[0038] Figures 13a-13d This invention relates to a practical application test of a heat sensing and collection device as a thermoelectric generator in the application of the method of printing heterogeneous structural materials on a combined sliding surface.

[0039] Figure 14 This invention relates to a practical application test of a heat sensing and collection device as a thermal sensor in the application of the method of printing heterogeneous structural materials on a combined sliding surface. Detailed Implementation

[0040] To provide a detailed description of the technical content, objectives, and effects of this invention, the following description will be provided in conjunction with the accompanying drawings.

[0041] like Figure 1 and Figure 2 As shown, in one aspect, the present invention provides a method for printing heterogeneous structural materials using a combination of movable and fixed sliding surfaces. The heterogeneous structural materials are prepared by vacuum filtration using a combination of movable and fixed sliding surfaces, specifically including the following steps:

[0042] S1. Preparation of polydimethylsiloxane prepolymer ink: Weigh the polydimethylsiloxane prepolymer and curing agent according to the set ratio, stir at room temperature for 10-20 min, then place in a vacuum drying oven and vacuum-store for a set time to obtain the polydimethylsiloxane prepolymer ink. The first set ratio is a weight ratio of 10:1, and the first set time is 30±5 min. A cross-linking reaction occurs after the polydimethylsiloxane prepolymer and curing agent are mixed. The pressure of the vacuum drying oven is 0.5–1 MPa.

[0043] S2. Preparation of a fixed sliding surface: Treat the polytetrafluoroethylene microporous filter membrane with 50-100W O2 plasma for 5-10 minutes. Fix the treated polytetrafluoroethylene microporous filter membrane on a direct writing printing stage as a printing substrate. Inject polydimethylsiloxane prepolymer ink into the ink container. Print according to the preset printing steps under a printing pressure of 0-50psi. Place the printed product in a constant temperature heating stage and heat until the polydimethylsiloxane prepolymer ink is cured to obtain a fixed sliding surface.

[0044] In a specific application embodiment, in step S2, the pore size of the polytetrafluoroethylene microporous filter membrane is adjusted according to the size of the dispersed phase particles in the first and second dispersion solutions, the needle diameter used in the printing process is selected according to the resolution requirements of the printed pattern, and the funnel is a sand core funnel.

[0045] In a specific application embodiment, in step S2, the heating temperature of the heating table is 85-90℃, the drying temperature of the drying oven is 85-90℃, and the drying time is 12-13h.

[0046] S3. Preparation of a movable sliding surface: The polyester film and trimethoxyfluorosilane liquid are placed in a vacuum drying dish for pretreatment. The pretreated polyester film is printed and placed on a heating stage to heat until the polydimethylsiloxane prepolymer ink is cured. The movable sliding surface is then separated from the polyester film to obtain the movable sliding surface.

[0047] In a specific application embodiment, in step S3, the size of the polyester film sheet is 6×6cm. 2 The pretreatment involves evacuating the vacuum desiccator to a vacuum state and placing it in a drying oven at 90±5℃ for 10-12 hours, followed by ultrasonic cleaning in a container of ethanol for 5-10 minutes.

[0048] S4. Controllable patterned assembly of the first thermoelectric material: According to the patterning requirements, the movable sliding surface prepared in step S3 is attached to the fixed sliding surface prepared in step S2 and fixed on the funnel. After being fully wetted, the first dispersion solution is poured into the funnel and vacuum filtered to complete the controllable patterned assembly of the first thermoelectric material and obtain a combined sliding surface with the first thermoelectric material.

[0049] S5. The second thermoelectric material is controllably patterned and assembled to form a heterostructure material: The movable sliding surface prepared in step S3 is moved to the area partially covered by the first thermoelectric material on the combined sliding surface with the first thermoelectric material prepared in step S4 and fixed on the funnel. After being fully wetted, the second dispersion solution is poured into the funnel for vacuum filtration. The second thermoelectric material is controllably patterned and assembled to form a heterostructure material.

[0050] In specific application embodiments, the first dispersion solution and the second dispersion solution are matrix solutions of heterogeneous structural materials, and the first dispersion solution and the second dispersion solution are deionized water, ethanol or methane.

[0051] A second aspect of the present invention provides a heterostructure material, which is prepared by a method of combined sliding surface printing of heterostructure materials.

[0052] A third aspect of the present invention provides a heat sensing and collection device comprising a heterostructure material, the heat sensing and collection device being a PN alternating thermoelectric generator. In preparing the heterostructure material, the PN alternating thermoelectric generator utilizes an N-type selenium-doped bismuth telluride dispersion as the first dispersion solution and a P-type antimony telluride dispersion as the second dispersion solution. Figure 3 A schematic diagram of the thermodynamic mechanism of the PN heterostructure material of the present invention is shown.

[0053] The following embodiments further describe the method and application of the present invention for printing heterogeneous structural materials on a combined sliding surface:

[0054] Example 1: Printability test of polydimethylsiloxane prepolymer ink.

[0055] The polydimethylsiloxane prepolymer and curing agent were mixed at a mass ratio of 10:1. After stirring at room temperature for 20 minutes, the mixture was placed in a vacuum drying oven and vacuum-preserved at a pressure of 1.0 MPa for 0.5 hours to eliminate air bubbles, thus obtaining the polydimethylsiloxane prepolymer ink.

[0056] A 0.22 μm pore size polytetrafluoroethylene (PTFE) microporous membrane was treated with 100W O2 plasma for 5 min to improve its wettability. The membrane was then fixed on a direct-write printing stage. PDMS was crosslinked at room temperature for 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, respectively, before being injected into ink containers. Printing was performed using 100 μm, 150 μm, and 300 μm diameter printing needles at minimal printing pressure according to the set printing program. After printing, the membrane was heated at 85°C for 15 min using a constant-temperature heating stage to gradually solidify the PDMS, resulting in a slip surface.

[0057] Example 2: Polydimethylsiloxane prepolymer and curing agent were mixed at a mass ratio of 10:1. After stirring for 20 minutes at room temperature, the mixture was placed in a vacuum drying oven and vacuum-stored at a pressure of 1.0 MPa for 0.5 hours to eliminate air bubbles and obtain polydimethylsiloxane prepolymer ink.

[0058] A 0.22 μm pore size polytetrafluoroethylene (PTFE) microporous membrane was treated with 100W O2 plasma for 5 min to improve its wettability. It was then fixed on a direct-write printing stage. PDMS was crosslinked at room temperature for 1 h, 2 h, 3 h, 4 h, 5 h, and 6 h, respectively, before being injected into ink containers. Printing was performed using 100 μm, 150 μm, and 300 μm diameter printing needles at minimal printing pressure according to the set printing program. After printing, the membrane was heated at 85°C for 15 min using a constant-temperature heating stage to gradually solidify the PDMS and obtain a slip surface. The PET sheet was then cut into 6×6 cm pieces.2 The PET was placed in a container filled with ethanol and ultrasonically cleaned for 5 min. 20 μL of trimethoxy(1H,1H,2H,2H-heptadecyl)silane was added dropwise to a vacuum desiccator, and the cleaned PET was placed in the desiccator. The equipment was evacuated and placed in a drying oven at 90°C for 12 h. Polydimethylsiloxane prepolymer ink was prepared at a weight ratio of 10:1. The treated PET was removed, and a patterned sliding surface was printed on its surface using direct writing technology. This surface served as a movable mask. The prepared sliding surface was placed on a heating stage and heated at 85°C for 15 min to fully cure it. The sliding surface was separated from the PET sheet and, according to the patterning requirements, attached to a fixed sliding surface.

[0059] Weigh 100 mg of N-type bismuth telluride (Bi₂Te₃) and 10 mg of sodium carboxymethyl cellulose (CMC-Na), disperse the mixture in 30 mL of deionized water, and stir on a magnetic stirrer at 400 rpm for 40 min to obtain a mixed solution. Sonicate the mixed solution at 100% power for 60 min to ensure thorough dispersion, obtaining an N-type bismuth telluride dispersion. Weigh 100 mg of P-type antimony telluride (Sb₂Te₃) and 10 mg of sodium carboxymethyl cellulose, and prepare a P-type antimony telluride (Sb₂Te₃) dispersion using the same method.

[0060] The assembled sliding surface was placed on a sand core funnel, and the airtightness of the device was tested using deionized water. The printed patterned sliding surface was then fixed on the sand core funnel and fully wetted. The treated N-type dispersion solution was poured into a solution bottle for vacuum-assisted filtration assembly to obtain a sliding surface with N-type thermoelectric material. This surface was then placed on a heating platform and dried at 70°C for 1 hour. The movable sliding surface was moved to cover the assembled N-type thermoelectric material portion. The P-type dispersion solution was then assembled in the blank area using the same method. After drying, an integrated PN alternating thermoelectric generator was obtained.

[0061] Following the experimental steps of Example 1, this invention was used to print with printing needles of 100μm, 150μm, and 300μm diameters. The relationship between the crosslinking time and minimum printing pressure of the polydimethylsiloxane prepolymer ink was tested. Qualitative tests were conducted on the curing degree, curing time, and contact state of the sliding surface in Example 1. Example 2 illustrates an application of the method of printing electro-heterogeneous structures using a combined sliding surface in thermoelectric devices. Example 2 underwent scanning electron microscopy characterization, optical microscopy characterization, energy dispersive X-ray spectroscopy testing, thermoelectric power generation testing, bending resistance testing, and heat sensing and collection testing. Specific conclusions are as follows:

[0062] Figure 4The graph shows the relationship between the crosslinking time and minimum printing force of the polydimethylsiloxane prepolymer ink prepared in Example 1, where the horizontal axis represents the crosslinking time and the vertical axis represents the printing force. The polydimethylsiloxane prepolymer and the curing agent are composed of a siloxane polymer and an alkaline catalyst, respectively. After thorough mixing, the catalyst reacts with the silicon-hydrogen bonds in the prepolymer, promoting crosslinking between the siloxane chains to form a fixed network structure. As time increases, the degree of crosslinking of the ink gradually increases, thus the printing parameters continuously change during the printing process. Figure 4 As shown, the printing pressure required for different sized printing needles varies with crosslinking time at room temperature (~25°C). When using a 100μm printing needle, the minimum printing pressure is between 13.5 and 55.5 psi; when using a 150μm printing needle, the minimum printing pressure is between 6.0 and 29.5 psi; and when using a 300μm printing needle, the minimum printing pressure is between 0 and 6.4 psi. The polydimethylsiloxane prepolymer ink maintains printability for a relatively long period at room temperature and exhibits good compatibility with direct-write printing. Furthermore, the dispensing system used in this embodiment can output printing pressures between 0 and 99 psi. The minimum unit for printing pressure adjustment is 0.01 psi within the 0–16.9 psi range, and 0.5 psi above 16.9 psi. Therefore, the control of the polydimethylsiloxane prepolymer ink is more precise at printing pressures below 16.9 psi.

[0063] Figures 5a-5b The infrared spectra of the polydimethylsiloxane prepolymer ink prepared in Example 1 at different curing times are shown, where the horizontal axis represents wavelength and the vertical axis represents transmittance. Figure 5a As shown, the infrared spectrum of the PDMS layer is characterized by methyl groups, exhibiting a peak at 2965 cm⁻¹. -1 Asymmetric stretching at 2900cm -1 Symmetrical tensile vibration at 1266cm -1 The sharper, stronger wavelength range belongs to the symmetric CH deformation vibration (umbrella mode) of the Si-CH3 group. 1423cm -1 and 1443cm -1 The two deformation zones of CH appear at 1043cm. -1 and 1112cm -1 The vibration observed at 790 cm⁻¹ indicates asymmetric tensile vibration of Si-O-Si. -1 The wavelength at 2157 cm⁻¹ is attributed to the tensile vibrations of Si-C in Si-CH₃. Furthermore, due to the unique ink properties of PDMS, it undergoes slow crosslinking at room temperature, which accelerates under heating conditions. The crosslinking reaction involves the connection between two H₂C=CH⁻ end groups and Si-H in the curing agent, thus appearing at 2157 cm⁻¹.-1 The strength of Si-H groups at the crosslinking site can quantitatively reflect the degree of PDMS crosslinking. For example... Figure 5b As shown, the strength of the Si-H groups increases with increasing curing time, indicating that more molecules participate in the crosslinking reaction, leading to more polymer chains covalently bonding to other curing agents. When the curing time of the slip surface is 10 min or more, the Si-H peak intensity does not change significantly. Therefore, the surface cured at 85℃ for 10 min is defined as a fully cured surface.

[0064] Figures 6a-6d The morphology of deionized water droplets falling on surfaces with different degrees of curing was recorded using a contact angle meter at the moment of droplet application on the slipping surface. Figure 6a A diagram showing the morphology of deionized water droplets falling onto an uncured, slipping surface. Figure 6b Morphological diagram of a droplet falling onto a sliding surface cured at 85°C for 1 minute. Figure 6c Morphological diagram of the slip surface cured at 85℃ for 2 min. Figure 6d The image shows the morphology of a droplet falling onto a sliding surface that has cured at 85°C for 10 minutes. Figure 6a As shown, water droplets falling on the uncured surface have a small contact angle and obvious wetting ridges at both the front and back contact lines. This is because PDMS is in a liquid state under uncured conditions and is easily deformable. A vertical component of surface tension is generated at the three-phase contact line between the droplet and the surface. The PDMS layer in this state cannot balance this vertical component without deformation, thus creating wetting ridges at the contact line. Large wetting ridges around the droplet lead to the depletion of the liquid PDMS slip layer, resulting in decreased liquid repellency. Furthermore, in this state, the droplet movement is in an adhesive state, making it difficult for the solute to leave the slip portion. This results in more solute being fixed in the slip portion during vacuum filtration assembly, leading to poor patterning effects. Figures 6b-6d As shown, with the increase of curing time, the contact angle between the droplet and the sliding surface increases, and the wetting ridges before and after the droplet decrease and gradually disappear. This indicates that during the curing process, the interaction force between the liquid and the solid surface gradually decreases. When vacuum filtration assembly is performed on the fully cured sliding surface, the solute will not be fixed after contacting the sliding surface, but will tend to move and eventually deposit in the blank part, forming a patterned deposition. Figures 7a-7d This image shows the morphology of deionized water droplets after they have fallen onto surfaces with different degrees of curing and been in contact with the surface for a certain period of time. The morphology of the water droplets on the surface was recorded every ten minutes. Figure 7a As shown, the droplets exhibit significant wetting ridges on the uncured sliding surface, which increase in size with increasing residence time. This indicates that the longer the residence time in this state, the more severe the damage to the liquid PDMS layer. Figures 7b-7dAs shown, with increasing curing degree, the wetting ridges gradually decrease and eventually disappear. This phenomenon is similar to the verification results of the previous experiment. Therefore, a fully cured sliding surface, i.e., heated at 85°C for 10 minutes or more, will have a longer service life and is more suitable as a patterned template.

[0065] Figures 8a-8f The images shown are scanning electron microscope (SEM) images of the sliding surface and sample in Example 2, and optical microscope images of the interface between the polydimethylsiloxane prepolymer ink and the N-type and P-type units. To analyze the patterning effect of the movable sliding surface in detail, the directly written printing sliding surface was cured to obtain the following... Figure 8a The fixed sliding surface is shown; after the movable sliding surface is removed, the following is obtained: Figure 8b and Figure 8c The P-type and PN-type structural units are shown. Figure 8e As shown, a clear boundary line was observed under a microscope between the printed polydimethylsiloxane prepolymer ink area and the unprinted blank area. The blank area on the right side exhibits some porosity, enabling rapid filtration of the dispersed solution under vacuum-assisted filtration. On the left side, it was clearly observed that the polydimethylsiloxane prepolymer ink had penetrated into the micropores of the filter membrane, demonstrating good barrier and slip properties. The interface between the P-type unit and PDMS obtained after the first vacuum filtration is shown in the image. Figure 8e As shown, the P-type unit boundaries are clear, and there is no Sb₂Te₃ residue in the PDMS portion; after the second filtration, the following was obtained: Figure 8f The N-type cells shown intersect with PDMS, with clear boundaries between the N-type cells and no Sb₂Te₃ or Bi₂Te₃ residues in the PDMS portion. Therefore, the fixed sliding surface of the direct-write printing, in conjunction with the movable sliding surface, forms an effective pattern and exhibits stability, enabling it to be used for multiple vacuum-assisted filtration processes.

[0066] Figures 9 and 10 show the energy dispersive X-ray spectra (EDS) of the N and P units of the sample in Example 2, where the horizontal axis represents X-ray energy and the vertical axis represents energy. Figures 9a-9d The surface morphology within the N-unit region is mapped to the elemental composition of Bi, Te, and Se atoms, as shown below. Figure 9e The EDS spectrum shows that the atomic composition of the N-type unit is: Bi atoms 54.76%, Te atoms 40.92%, and doped Se atoms 4.32%. EDS analysis confirms that the N-type unit is a Se-doped Bi₂Te₃ material. Figures 10a-10c This represents the result of the elemental mapping between the surface morphology and Sb and Te atoms in this region. Figure 10dThe EDS spectrum of the P-type unit shows that the atomic content of Sb is 39.22% and that of Te is 60.78% based on the atomic ratio in the inset. EDS testing confirms that the material of the P-type unit is pure Sb₂Te₃, and the heat sensing and collection device is a heterostructure.

[0067] Figures 11a-11d For testing the bending performance of heat sensing and collection devices, such as Figure 11a As shown, the deposited Sb₂Te₃ and Bi₂Te₃ materials did not exhibit warping or fracture under significant bending conditions, demonstrating high flexibility. However, to ensure the long-term utilization of this characteristic in thermoelectric devices, sustainable performance must be demonstrated through multiple cycle simulations. Figure 11b and Figure 11c As shown, the two ends of the thermoelectric device are fixed to the reciprocating motor, and a displacement of 15mm is set. Figure 11c The bending state of the device was simulated through a continuous bending and recovery process, illustrating the usage of the flexible device. For example... Figure 11d As shown, the resistance change of the thermoelectric device increases slowly with the increase of the number of bends. The bending resistance change within 6000 bends is less than 0.2, indicating that the Sb2Te3 and Bi2Te3 materials deposited on the surface have a stable state on the substrate during the bending process and no serious fracture occurs. The device exhibits good electrical stability and durability.

[0068] Figures 12a-12d For testing the thermoelectric performance of heat sensing and collection devices, due to the inherent differences in properties between P-type and N-type semiconductors, when a temperature difference is generated across the two ends of a PN junction, holes in the P-type semiconductor move from the hot end to the cold end, exhibiting a thermoelectric electromotive force (EMF) pointing from the high-temperature end to the low-temperature end; while free electrons in the N-type semiconductor move from the hot end to the cold end, exhibiting a thermoelectric EMF pointing from the low-temperature end to the high-temperature end. This is achieved through the use of... Figure 12a The experimental setup shown was used to test the power generation performance of a thermoelectric generator containing a PN junction. One end of the thermoelectric device was heated by the metal material within the red box, serving as the hot end; the area within the blue box was suspended in the air, and a layer of insulating material was adhered between the glass plate and the device, serving as the cold end. Figure 12b This is a side view of the experimental setup. The fabricated PN alternating type generator senses the temperature difference between its two ends under the Seebeck effect and converts heat into electrical energy. First, a thermoelectric device containing a pair of PN structures was tested, and the results are as follows... Figure 12c As shown, a 0.2mV open-circuit voltage is initially generated at a temperature difference of 5K, and the open-circuit voltage is linearly related to the temperature difference. A voltage of 1.97mV is generated when the temperature difference increases to 65K. The open-circuit voltages generated by the three pairs of PN structures with temperature difference are as follows: Figure 12dAs shown, an open-circuit voltage of 0.9 mV is generated at a temperature difference of 5 K, and a maximum voltage of 6 mV is generated when the temperature difference is increased to 65 K. Although more PN structures mean more PN contact points are required, there is no reduction in thermoelectric performance. This is because the thermoelectric material assembled by vacuum filtration is uniformly distributed on the substrate, and the generated open-circuit voltage is comparable to the output of flexible devices reported in previous literature. The alternating PN units are connected to the vacuum-assisted filtration through patterning, so no additional cutting and assembly is required, which has special advantages in terms of overall device size design and ease of manufacturing.

[0069] Figures 13a-13d To test the practical application of the heat sensing and collection device prepared in Example 2 as a thermoelectric generator, three pairs of heat sensing and collection devices were packaged to form a thermoelectric generator assembly. The packaged thermoelectric generator was then attached to the arm, as shown in the image. Figure 13a and Figure 13b As shown, a stable voltage of 0.9mV is generated upon contact with the arm; as Figure 13c and Figure 13d The same thermoelectric generator was placed above a beaker containing 100°C hot water. After sensing the heat source, the generator generated an open-circuit voltage of 38.1mV. The experiment shows that the open-circuit voltage has a wide temperature detection range and has the potential to be used as a heat source detection device. It is expected to be applied to self-powered environmental monitoring to prevent natural disasters such as fires.

[0070] Figure 14 This study investigates the practical application of the heat sensing and collection device prepared in Example 2 as a thermal sensor. Figure 14 Part a shows the voltage response of the heat sensing and collection device under finger touch, with the frequency of finger contact and removal controlled at 1 second per touch. The experimental results show that the open-circuit voltage increases and decreases sharply with finger touch, indicating that the device is very sensitive to changes in external temperature. Figure 14 Section b shows a magnified display of the voltage change results over 15-20 seconds. The inset illustrates the operation of touching and removing the device. When a finger is fully pressed against one side of the device for heating, the open-circuit voltage of the paper reaches approximately 0.5mV. The response time, from the start of finger contact to the maximum open-circuit voltage, is approximately 0.452s; the recovery time, from finger removal to the open-circuit voltage returning to zero, is approximately 0.421s. The maximum voltage varies in each cycle due to slight differences in temperature change caused by each finger touch. This heat sensing and collection device, acting as a paper-based thermal sensor, enables self-powered control of wearable electronic devices.

[0071] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for printing heterogeneous structural materials using a combined sliding surface, characterized in that, Heterogeneous structural materials are prepared by vacuum filtration using a combination of movable and fixed sliding surfaces, specifically including the following steps: S1. Preparation of polydimethylsiloxane prepolymer ink: Weigh polydimethylsiloxane prepolymer and curing agent according to the set ratio, stir at room temperature for 10-20 minutes, put into a vacuum drying oven, and then vacuum store for a set time to obtain polydimethylsiloxane prepolymer ink. S2. Preparation of a fixed sliding surface: Treat the polytetrafluoroethylene microporous filter membrane with 50-100W O2 plasma for 5-10 minutes. Fix the treated polytetrafluoroethylene microporous filter membrane on a direct writing printing stage as a printing substrate. Inject the polydimethylsiloxane prepolymer ink into the ink container. Print according to the preset printing steps under a printing pressure of 0-50 psi. Place the printed product in a constant temperature heating stage and heat until the polydimethylsiloxane prepolymer ink is cured to obtain a fixed sliding surface. S3. Preparation of a movable sliding surface: The polyester film and trimethoxyfluorosilane liquid are placed in a vacuum drying dish for pretreatment. The pretreated polyester film is printed and placed on a heating table and heated until the polydimethylsiloxane prepolymer ink is cured. The movable sliding surface is then separated from the polyester film to obtain the movable sliding surface. S4. Controllable patterned assembly of the first thermoelectric material: According to the patterning requirements, the movable sliding surface prepared in step S3 is attached to the fixed sliding surface prepared in step S2 and fixed on the funnel. After being fully wetted, the first dispersion solution is poured into the funnel and vacuum filtered to complete the controllable patterned assembly of the first thermoelectric material and obtain a combined sliding surface with the first thermoelectric material. S5. Controllable patterned assembly of the second thermoelectric material to form a heterogeneous structure material: The movable sliding surface prepared in step S3 is moved to the area partially covered by the first thermoelectric material on the combined sliding surface with the first thermoelectric material prepared in step S4 and fixed on the funnel. After being fully wetted, the second dispersion solution is poured into the funnel for vacuum filtration to complete the controllable patterned assembly of the second thermoelectric material to form a heterogeneous structure material. The pore size of the polytetrafluoroethylene microporous filter membrane is adjusted according to the size of the dispersed phase particles in the first dispersion solution and the second dispersion solution, and the needle diameter used in the printing process is selected according to the resolution requirements of the printed pattern; the first dispersion solution and the second dispersion solution are both matrix solutions of heterogeneous structural materials.

2. The method for printing heterogeneous structural materials via a combined sliding surface according to claim 1, characterized in that, The set ratio is a weight ratio of 10:1, and the set time is 30±5min.

3. The method for printing heterogeneous structural materials via a combined sliding surface according to claim 1, characterized in that, In step S1, the polydimethylsiloxane prepolymer and the curing agent undergo a crosslinking reaction after being mixed, and the pressure of the vacuum drying oven is 0.5~1MPa.

4. The method for printing heterogeneous structural materials via a combined sliding surface according to claim 2, characterized in that, In step S3, the heating temperature of the heating table is 85-90℃, and in step S1, the drying temperature of the vacuum drying oven is 85-90℃, and the drying time is 12-13h.

5. The method for printing heterogeneous structural materials via a combined sliding surface according to claim 1, characterized in that, In step S3, the size of the polyester film sheet is 6×6cm. 2 The pretreatment involves evacuating the vacuum desiccator to a vacuum state and placing it in a drying oven at 90±5℃ for 10-12 hours, followed by ultrasonic cleaning in a container filled with ethanol for 5-10 minutes.

6. A heterogeneous structural material, characterized in that, The heterostructure material is prepared by the method of printing heterostructure material by combined sliding surface as described in claim 1.

7. A heat sensing and collection device comprising the heterogeneous structural material of claim 6, characterized in that, The heat sensing and collection device includes the heterostructure material, and the heat sensing and collection device is a PN alternating thermoelectric generator.

8. The heat sensing and collection device according to claim 7, characterized in that, The PN alternating thermoelectric generator uses an N-type selenium-doped bismuth telluride dispersion as the first dispersion solution and a P-type antimony telluride dispersion as the second dispersion solution when preparing heterostructure materials.

Citation Information

Patent Citations

  • Method of transferring a membrane image to an article in a membrane image transfer printing process

    CN1938159A

  • Inkjet printing on polycarbonate substrates

    EP3663095A1